Can a bleaching toothpaste containing Blue Covarine demonstrate the same bleaching as conventional techniques? An in vitro, randomized and blinded study - Rached Dantas, Andrea Abi [UNESP]; Bortolatto, Janaina Freitas [UNESP]; Roncolato, Avery [UNESP]; Merchan, Hugo [UNESP]; Floros, Michael Christopher; Kuga, Milton Carlos [UNESP]; Oliveira Junior, Osmir Batista de [UNESP] (Univ Sao Paulo Fac Odontologia Bauru, 2015)
Objective: The purpose of this in vitro study was to compare the efficacy of a bleaching 1/4.,1 toothpaste containing Blue Covarine vs. conventional tooth bleaching techniques using peroxides (both in-office and at-home). Material and Methods: Samples were randomly distributed into five experimental groups (n=15): C- Control; BC- Bleaching toothpaste containing Blue Covarine; WBC- Bleaching toothpaste without Blue Covarine; HP35 In-office bleaching using 35% hydrogen peroxide; and CP10- At-home bleaching with 10% carbamide peroxide. The dental bleaching efficacy was determined by the color difference (Delta E), luminosity (Delta L), green-red axis (Delta a), and blue-yellow axis (Delta b). The CIELab coordinates were recorded with reflectance spectroscopy at different times: TO- baseline, T1- immediately after bleaching, T2- 7 days, T3- 14 days, and T4- 21 days after the end of treatments. Data were analyzed by a repeated measures mixed ANOVA and post hoc Bonferroni test, with a significance level of 5%. Results: No significant differences were found between the treatment groups C, BC, and WBC. The groups HP35 and [P10 showed significantly higher whitening efficacy than groups C, BC, and WBC. Conclusions: There were no significant differences in the whitening efficacy between a Blue Covarine containing toothpaste, a standard whitening toothpaste, and a control. Neither of the whitening toothpastes tested were as effective as in-office or at-home bleaching treatments.
Keywords: Tooth bleaching; Dentifrices; Color; Efficacy; Spectrophotometers